Identification of the Cause of the Fire of Four Tank Units at PT. Tox with the Fishbone and Domino's Factory Method - Mudji Kusumaningrum, Nina; Adelia, Chika; Agus Setiawan, Ripal; Azmi, Fauzan; Sulistiyo Nugroho, Budi (Advances In Social Humanities Research, 2024)
The oil and gas industry is prone to workplace accidents such as explosions and fires. PT TOX experienced a fire in an oil tank that had an impact on the environment and surrounding living things. This research uses a qualitative approach with fishbone analysis and domino's factory method to evaluate the cause of the fire. Data was collected through scientific journals and related news based on online databases. The results of the analysis using the fishbone diagram analysis method showed that the causes of the fire included leaks that spread gas vapors, inadequate operator response, absence of early detection (such as gas detectors and automatic alarms), damage to the tank structure, and volatile and flammable chemicals. To support further identification, researchers used the domino's factory analysis method which revealed factors such as poorly prepared management, tank corrosion, and unsafe actions such as moving products without safe procedures. The fire caused huge losses, including the destruction of four tanks by fire. Prevention of workplace accidents, especially fires, in the future can be done with regular training for operators, the use of fire protection equipment, periodic inspections, and revision of emergency response SOPs